Effect of bone marrow mesenchymal stem cells transplantation on BMP-15 expression and Graafian follicle count in mice model of endometriosis - Ratriana Via Parasti; Widjiati Widjiati; Sri Ratna Dwiningsih (Majalah Obstetri dan Ginekologi, 2018)
Objectives: To determine the effect of bone marrow mesenchy-mal stem cells (BMSCs) on BMP-15 expression and Graafian follicle count in endometriosis mice.Material and Methods: This study was a laboratory randomized clinical trial on Mus musculus. The object of the study was 42 mice which were divided into 3 groups, the control, endome-triosis, and endometriosis + BMSCs groups. Comparison of BMP-15 expression and Graafian follicle count between groups was evaluated.Results: Immunohistochemical analysis showed that BMP-15 expression in control, endometriosis, and endometriosis + BMSCs groups had p=0.551, p=0.446 and p=0.917 with ANOVA test p=0.273, indicating no statistically significant differences between groups . Graafian follicular count in the three groups had p=0.31, p=0.001, and p=0.006, with the Kruskal-Wallis test p=0.001. Graafian follicles in the endometriosis + BMSCs group were higher than those in control and endometriosis groups.Conclusion:In the endometriosis mouse model with bone mar-row stem cell transplantation the BMP-15 expression in each group did not show a difference, but a significant difference was found in the number of Graafian follicles.